Estimating Factors Related to Fluoroquinolone Resistance Based on One Health Perspective: Static and Dynamic Panel Data Analyses From Europe - Zhang, Dandan; Cui, Youwen; Zhang, Xinping (Frontiers in Pharmacology, 2019)
Abstract Objectives: Antimicrobial resistance (AMR) has become a One Health problem in which fluoroquinolones resistance have caused great concern. The aim of this study is to estimate factors related to fluoroquinolones resistance involving the professionals and antimicrobial consumption (AMC) in human and animal fields. Methods: A country-level panel dataset in Europe from 2005 to 2016 was constructed. The dependent variables were measured by Escherichia coli (E. coli) and Pseudomonas aeruginosa (P. aeruginosa) resistance rates to fluoroquinolones. Both the static and dynamic panel data models were employed to estimate above factors associated with the resistance rates. Results: The 10% increase in the number of medical staff and veterinary professionals per 100,000 populations were significantly correlated with the 32.44% decrease of P. aeruginosa and 0.57% decrease of E. coli resistance rates to fluoroquinolones (Coef. = -3.244, -0.057; p= 0.000, 0.030, respectively). The 10% increase in the human AMC was correlated with 10.06% and 8.04% increase of P. aeruginosa resistance rates to fluoroquinolones in static and dynamic model (Coef. = 1.006, 0.804; p= 0.006, 0.001, respectively). The 10% increase in veterinary AMC was related to 1.65% decrease of P. aeruginosa resistance rates to fluoroquinolones (Coef. = -0.165; p= 0.019). Conclusions: The increase of medical and veterinary professionals are respectively associated with the decrease of P. aeruginosa and E. coli resistance rates to fluoroquinolones. The increase in human AMC is also associated with increase of P aeruginosa resistance rates, while the increase in veterinary AMC was found to be associated with a decrease in resistance rate for P. aeruginosa.